Study the Level of Patients’ Service Satisfaction of Luang Prabang Provincial Hospital: https://doi.org/10.69692/SUJMRD1003193 - kanmany, vone; Keoboualapheth, Soulideth; Silivanh, Sommay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research was to study the level of patients’ service satisfaction of Luang Prabang provincial hospital and comparison of patients’ service satisfaction classified by personal information of Luang Prabang provincial hospital. The samples of this study were 385 patients and their relatives who received services at the Luang Prabang provincial hospital. The research were using the questionnaire as a tool to collect data. Data were analyzed by using mean, standard deviation, T-test, F-test (One-way ANOVA). Finding indicated that the overall opinion on service satisfaction was at a median level patient in Luang Prabang provincial hospital. The respondent with different personal demographic data by sex, status, age, education, occupation, income, and types of patient care; were no different in service satisfaction; but the respondent with different personal demographic data by who services at each unit were different in service satisfaction.